Periodic extreme Gibbs measures with memory length 2 of Vannimenus model - Akin, Hasan; Ganikhodjaev, Nasir; Uguz, Selman; Temir, Seyit (2011)
In this paper we investigate extreme Gibbs measures with period p for the Vannimenus model.